Inhibition of 6-Methylsulfinylhexyl Isothiocyanate for Cell Cycle Progression in Quiescent JB6 Cells Stimulated with Fetal Bovine Serum, Accompanied by Suppression of Cyclin A2 Expression - Takashi Hashimoto; Maki Kobayashi; Kazuki Kanazawa (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
6-Methylsulfinyhexyl isothiocyanate (6-MSITC) is a specific compound in Wasabi (Wasabia japonica Matsumura). 6-MSITC showed the inhibition of cell cycle progression stimulated with epidermal growth factor in quiescent JB6 cells. The objective of the present study is to investigate inhibitory effects of 6-MSITC on cell cycle progression stimulated with fetal bovine serum (FBS) and the mechanism. 6-MSITC inhibited FBS-stimulated cell cycle progression in quiescent JB6 cells serum-starved for 36 h. However, treatment with 6-MSITC did not affect the G1 phase check point-related proteins including Rb protein, cyclin D1, cyclin D2, cyclin D3, CDK4, CDK6, p16, p21 and p27, and cell growth signal through Akt and MAPK pathways. On the other hand, 6-MSITC inhibited the gene expression in DNA synthesis-related proteins such as cyclin A2, resulting in decrease the DNA polymerase activity. These results indicate that 6-MSITC inhibits the FBS-stimulated cell cycle progression from G0 phase to S phase accompanied by the suppression of gene expression of cyclin A2 in quiescent JB6 cells